Abundance and diversity of decapod crustaceans in the deep-Catalan Sea (Western Mediterranean) - Cartes, Joan Enric; Sardà, Francisco (Journal of Natural History, 1992)
20 pages, 5 figures, 7 tables The deep-slope decapod fauna of the Catalan Sea was extensively sampled with an OTSB-14 bottom trawl. A total of 67 bottom tows were taken from 1985 to 1989 at bottom depths ranging from 552 to 2261 m. Species in which abundance decreased with depth were Plesionika acanthonotus, Polycheles typhlops, Calocaris macandreae and Geryon longipes. Highest densities of Acanthephyra eximia, Stereomastis sculpta, and Nematocarcinus exilis were attained at the greatest depths studied. Total abundance, biomass and species richness for decapod crustaceans as a whole decreased with depth. Maximum decapod biomass and diversity occurred on the upper-middle slope on soft bottoms in the.Catalan Sea and in all regions for which data were available. In the Catalan Sea, an oligotrophic area, the abundance of decapods as a group seemed to be higher than in north- Atlantic eutrophic regions. In these latter areas, other deep-sea benthic invertebrate groups, particularly ophiuroids, predominate. © 1992 Taylor & Francis Ltd.